Growth and Yield Response of Melon to Different Time Application of Goat Manure and Dose of Potassium - Handajaningsih, Merakati; Marwanto, Marwanto; Armitasari, Tri; Inoriah, Entang; Pujiwati, Hesti (Akta Agrosia, 2018)
Goat manure contains high potassium, thus it is expected to reduce  the usage of synthetic potassium fertilizer. Incubation of goat manure is needed prior to planting since the nutrients are slow release. The objective of the experiment was to find the best time application and dose of potassium on growth and yield of melon. Container experiment using polybags was set in Completely Randomized Design.  Goat manure were incorporated into soil at the time of transplanting (0 DBT), 5 days before transplanting (5 DBT), and 10 DBT. The dose of potassium was consisted of 0 kg/ha, 200 kg/ ha and 400 kg/ha. The treatments were repeated 3 times, each of which consisted of 4 plants. Growth and yield of plants showed no response to the interaction between the two factors of treatment. Single effect of time applicaton of goat manure 10 DBT affected leaf area (1619.51 cm2), fruit weight (872 g), fruit diameter (16.19 cm) and the thickness of edible fruit part (2.61 cm). The dose of potassium 400 kg/ha increased fruit sweetness to 8.20Brix.